2021
DOI: 10.3390/jcm10215074
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome in Chronic Coronary Syndrome Patients

Abstract: Despite knowledge of classical coronary artery disease (CAD) risk factors, the morbidity and mortality associated with this disease remain high. Therefore, new factors that may affect the development of CAD, such as the gut microbiome, are extensively investigated. This study aimed to evaluate gut microbiome composition in CAD patients in relation to the control group. We examined 169 CAD patients and 166 people in the control group, without CAD, matched in terms of age and sex to the study group. Both populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
5
15
0
Order By: Relevance
“…14) The results highlighted the participation of TMAO in CHD development and advised that TMAO tests were available for CHD patients to improve management and prognosis. In the current study, the results showed no significant difference in microbial abundance among the two groups by alpha and beta biodiversity analysis, which was in line with the founding of Wan, et al 15) However, a randomized trial, 16) which enrolled 169 CHD patients and 166 people without CHD, revealed that the CHD group was characterized by a lower number of OTUs compared with the control. This article was based on the Poland population, which may be the reason for different findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…14) The results highlighted the participation of TMAO in CHD development and advised that TMAO tests were available for CHD patients to improve management and prognosis. In the current study, the results showed no significant difference in microbial abundance among the two groups by alpha and beta biodiversity analysis, which was in line with the founding of Wan, et al 15) However, a randomized trial, 16) which enrolled 169 CHD patients and 166 people without CHD, revealed that the CHD group was characterized by a lower number of OTUs compared with the control. This article was based on the Poland population, which may be the reason for different findings.…”
Section: Discussionsupporting
confidence: 91%
“…18) Previous studies have shown a decrease in the Bacteroidetes phylum and an increase in the Firmicutes phylum in coronary artery disease. 16,19) This study found a reduction in the abundance of Bacteroidetes in the CHD group, similar to the study by Jie,20) in which stool samples were collected from 218 patients with coronary artery disease and 187 healthy controls. Although Firmicutes abundance did not differ between study groups, the results of the current study confirmed a higher relative abundance of Firmicutes in the control group contrary to previously mentioned findings provided by Sawicka-Smiarowska.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Firmicutes/Bacteroidetes ratio [19,[83][84][85][86][87][114][115][116][121][122][123]. A higher value was found to be related to abnormal body weight, lack of physical activity, and female gender (Figure 1) [19,[52][53][54]90,112,113].…”
Section: Firmicutes/bacteroidetes Ratiomentioning
confidence: 98%
“…In the literature, different gut microbiota were related to risk factors, particularly for cardiovascular diseases; however, one of the most common results is a change in the Firmicutes/Bacteroidetes ratio [19,[83][84][85][86][87][114][115][116][121][122][123]. A higher value was found to be related to abnormal body weight, lack of physical activity, and female gender (Figure 1) [19,[52][53][54]90,112,113].…”
Section: Firmicutes/bacteroidetes Ratiomentioning
confidence: 99%